Spatial predictions of land‐use transitions and associated threats to biodiversity: the case of forest regrowth in mountain grasslands. Issue 2 (21st June 2012) - Pellissier, Loïc; Anzini, Maruska; Maiorano, Luigi; Dubuis, Anne; Pottier, Julien; Vittoz, Pascal; Guisan, Antoine; Cousins, Sara
Abstract Question Can we predict where forest regrowth caused by abandonment of agricultural activities is likely to occur? Can we assess how it may conflict with grassland diversity hotspots? Location Western Swiss Alps (400–3210 m a.s.l.). Methods We used statistical models to predict the location of land abandonment by farmers that is followed by forest regrowth in semi‐natural grasslands of the Western Swiss Alps. Six modelling methods (GAM, GBM, GLM, RF, MDA, MARS) allowing binomial distribution were tested on two successive transitions occurring between three time periods. Models were calibrated using data on land‐use change occurring between 1979 and 1992 as response, and environmental, accessibility and socio‐economic variables as predictors, and these were validated for their capacity to predict the changes observed from 1992 to 2004. Projected probabilities of land‐use change from an ensemble forecast of the six models were combined with a model of plant species richness based on a field inventory, allowing identification of critical grassland areas for the preservation of biodiversity. Results Models calibrated over the first land‐use transition period predicted the second transition with reasonable accuracy. Forest regrowth occurs where cultivation costs are high and yield potential is low, i.e. on steeper slopes and at higher elevations. Overlaying species richness with land‐use change predictions, we identified priority areas for the management and conservation of biodiversity at intermediate elevations. Conclusions Combining land‐use change and biodiversity projections, we propose applied management measures for targeted/identified locations to limit the loss of biodiversity that could otherwise occur through loss of open habitats. The same approach could be applied to other types of land‐use changes occurring in other ecosystems.